2002
DOI: 10.2105/ajph.92.9.1421
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Injury and Illness Surveillance: Conceptual Filters Explain Underreporting

Abstract: Occupational health surveillance data are key to effective intervention. However, the US Bureau of Labor Statistics survey significantly underestimates the incidence of work-related injuries and illnesses. Researchers supplement these statistics with data from other systems not designed for surveillance. The authors apply the filter model of Webb et al. to underreporting by the Bureau of Labor Statistics, workers' compensation wage-replacement documents, physician reporting systems, and medical records of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
478
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(510 citation statements)
references
References 67 publications
16
478
1
5
Order By: Relevance
“…2,9 Reports from the Occupational Safety and Health Administration (OSHA), the only source of health statistics for the industry, do not count symptoms or illnesses that are considered by the worker or supervisor to be unrelated to work. 10 Suspected undercounts of injury and illness are corroborated by published studies of Latino poultry processing workers indicating that 60% of workers reported symptoms indicative of work-related illness. 11 Recent congressional hearings on occupational injury and illness undercounts concluded that as much as 69% of injuries and illnesses never find their way into the OSHA statistical summaries.…”
Section: Introductionmentioning
confidence: 77%
“…2,9 Reports from the Occupational Safety and Health Administration (OSHA), the only source of health statistics for the industry, do not count symptoms or illnesses that are considered by the worker or supervisor to be unrelated to work. 10 Suspected undercounts of injury and illness are corroborated by published studies of Latino poultry processing workers indicating that 60% of workers reported symptoms indicative of work-related illness. 11 Recent congressional hearings on occupational injury and illness undercounts concluded that as much as 69% of injuries and illnesses never find their way into the OSHA statistical summaries.…”
Section: Introductionmentioning
confidence: 77%
“…We believe that our study definition for work-related CTS, which relies on self-reported attribution of the case to work by a clinician, is conservative because there are many barriers (or filters) to recognition of a condition as work-related by a clinician [Azaroff et al, 2002]. When physicians were asked to report all cases of work-related CTS to the Massachusetts Department of Public Health, there was evidence of significant underreporting, which may at least partially reflect under-recognition of work-relatedness [Davis et al, 2001].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Under-reporting of occupational disease is known to be high in many jurisdictions [Shannon and Lowe, 2002;Biddle and Roberts, 2003;Morse et al, 2004;Réseau 'Surveiller les Cancers d'Origine Professionnelle en Seine Saint-Denis' (GISCOP93), 2005], although a significant number of acute injuries have also been shown to go underreported in Canada [Shannon and Lowe, 2002;Vézina et al, 2011] and the United States [Azaroff et al, 2002]. In highly adversarial systems even those suffering from acute trauma as a result of obvious industrial accidents may well be submitted to abusive contestation and suggestions of ''moral hazard,'' strategies that contribute to underreporting [Boden et al, 2001].…”
Section: Discourses Underpinning Workers' Compensation Systemsmentioning
confidence: 99%